EFFECT OF Na2So4 ON THE GROWTH, WATER RELATIONS, PROLINE, TOTAL SOLUBLE SUGARS AND ION CONTENT OF ATRIPLEX HALIMUS SUBSP. SCHWEINFURTHII THROUGH IN VITRO CULTURE - Nedjimi, Bouzid; Daoud, Youcef (Anales de Biología, 2006)
Atriplex halimus subsp. Schweinfurthii is a perennial halophyte, which is widely distributed in the Algerian salt steppes. This study reports the effect of sodium sulphate (Na2SO4) on the growth, tissue water content, proline, total soluble sugars and ion content of the species under in vitro conditions. Optimal growth was observed at 50mM Na2SO4 and declined with a further increase in salinity. Water potential (Ψw) of plants became more negative with an increase in salinity. Ca2+, Mg2+, and K+ concentration of plants decreased with increasing salinity, while Na+ and SO42- increased. Both proline and total soluble sugars content of shoots and roots were highest at 250 mM Na2SO4. This study has demonstrated that salt tolerance in A. halimus subsp. Schweinfurthii is achieved by appropriate osmotic adjustment involving accumulation of inorganic and organic solutes. At high salinities, growth reduction probably occurs as a result of high concentrations of Na< sup>+ and SO42- and their interference with other ions such as K+. This variety can be used locally as a fodder for livestock and could be useful in sand dune stabilization.